Cost and Benefit of Information Search using Two Different Strategies - Paulus Insap Santosa (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
Searching for information is one major Internet activities during which information seekers may gain benefit as well as incurred some cost. In general, information seekers seldom employ any search strategy for general browsing to explore information space. On the other hand, in certain situation, they may employ certain search strategy, especially those who engage in a fact-finding activity. The objective of this research is to shed light on how search strategy can be used to gain the maximum benefit of information search activities. It borrows the two-factor theory to group Web design elements into benefit and cost manifested as motivating and hygiene factors. This research employed a laboratory experiment with 235 respondents who were participated on this research voluntarily. Respondents were divided into two groups, namely ‘plan-group’ and ‘unplan-group’. Both groups were given certain tasks related to information search. The experiment was followed by a post experiment survey. The result shows that respondents who were in the ‘plan-group’ perceived less benefit and incurred more cost compared to those in the ‘unplan-group’. The future research is proposed at the end of this manuscript.